Ruminal characteristics and feedlot performance of steers during accelerated step-up to high-concentrate diets using Megasphaera elsdenii (Lactipro advance). - Ellerman, Tara Jo (Kansas State University, 2017)
Ruminal characteristics and feedlot performance were measured for steers adapted to a high-grain diet using a traditional 22-d step-up program (Control) and for steers adapted over 10 d with the aid of M. elsdenii NCIMB 41125 fresh culture administered as an oral gavage (Fresh), an oral gavage of rehydrated lyophilized culture (Rehyd), or Rehyd combined with lyophilized culture powder administered daily as a ration top-dress (Rehyd+Daily). Yearling steers (n = 435; initial BW = 408 ± 5 kg) were blocked by weight and randomly allocated to 64 concrete surfaced pens with 7 steers/pen and 16 pens/treatment. Step-up diets contained 40, 30, and 20% corn silage, and were followed by a finishing diet containing 10% corn silage and 90% concentrate. Ruminal fluid was obtained from a subset of steers by rumenocentesis 26 h after their first feeding, and inoculated into culture tubes containing lactate medium to determine differences in capacity for lactate metabolism over 24 h. A radiofrequency pH bolus was placed in the reticulorumen of 32 steers, that measured ruminal pH every 10 min for 124 d. Steers were fed once daily ad libitum for 156 d, then weighed, and transported 450 km to a commercial abattoir for harvest. HCW and incidence of liver abscesses were determined at harvest and carcass traits were evaluated after 36 h of refrigeration. No differences were detected for feedlot performance (P > 0.20), liver abscesses (P = 0.45), or carcass traits (P > 0.20). Capacity for lactate utilization was increased with all forms of M. elsdenii, as evidenced by increases in optical density (absorbance) of M. elsdenii cultures, disappearance of lactate, and increase in butyrate production (P < 0.01). Steers on Rehyd and Rehyd+Daily treatments spent less time between pH thresholds of 5.6 > pH > 5.2 (P < 0.01); 5.2 > pH > 5.0 (P < 0.01); and pH < 5.0 (P < 0.01) than Controls throughout the finishing period. In conclusion, steers dosed with M. elsdenii can be stepped up to finishing diets in 10 d with no adverse effects on performance. Ruminal fluid containing fresh cultures or freeze-dried and rehydrated cultures of M. elsdenii NCIMB 41125 were equally effective in metabolizing lactic acid. Lyophilized M. elsdenii resulted in less time below important pH thresholds, but no further benefit of daily administration was realized in this experiment.
Keywords: Megasphaera elsdenii; Feedlot; Lactipro advance; Accelerated step-up